Reduced antiviral seropositivity among patients with inflammatory bowel disease treated with immunosuppressive agents. (3rd April 2023) - Shiga, Hisashi; Takahashi, Takahiro; Shiraki, Manabu; Kojima, Yasuhiro; Tsuji, Tsuyotoshi; Takagi, Sho; Hiramoto, Keiichiro; Yokoyama, Naonobu; Sugimura, Mikako; Iwabuchi, Masahiro; Endo, Katsuya; Onodera, Motoyuki; et al.
Abstract: Background: Although live-attenuated vaccines are contraindicated under immunosuppression, the immune status of patients with inflammatory bowel disease (IBD) has not been fully assessed prior to immunosuppressive therapy. Aims: To investigate antiviral serostatus against viruses requiring live vaccines for prevention in IBD patients undergoing immunosuppressive therapy. Methods: This multicenter study included IBD patients who were aged <40 years and were treated with thiopurine monotherapy, molecular-targeted monotherapy, or combination therapy. Gender- and age-matched healthy subjects (HS) living in the same areas were included as control group. Antibody titers against measles, rubella, mumps, and varicella were measured by enzyme-linked immunosorbent assays. Results: A total of 437 IBD patients (163 ulcerative colitis [UC] and 274 Crohn's disease [CD]) and 225 HS were included in the final analysis. Compared with HS, IBD patients had lower seropositivity rates for measles (IBD vs. HS = 83.91% vs. 85.33%), rubella (77.55% vs. 84.89%), mumps (37.50% vs. 37.78%), and varicella (91.26% vs. 96.44%). Gender- and age-adjusted seropositivity rates were lower in UC patients than in both CD patients and HS for measles (UC, CD, and HS = 81.60%, 85.29%, and 85.33%), rubella (76.40%, 78.23%, and 84.89%), mumps (27.16%, 43.70%, and 37.78%), and varicella (90.80%, 91.54%, and 96.44%); the difference was significant for all viruses except measles. Divided by the degree of immunosuppression, there were no significant differences in seropositivity rates among IBD patients. Conclusions: IBD patients, especially those with UC, exhibit reduced seropositivity rates and may benefit from screening prior to the initiation of immunosuppressive therapy.